PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS DENGAN METODE ROLE PLAYING - Marlina, Tessi; Zuardi, Zuardi; Indrawati, Tin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
THE IMPROVEMENT OF STUDENT LEARNING OUTCOMES IN IPS LEARNING WITH ROLE PLAYING METHOD AbstrackThe purpose of the research was  to describe the student’s learning outcomes in IPS learning with role playing method in the fifth grade of  SDN 13 Guguak VIII Koto. The kind of the research was Classroom action research that use quantitative and qualitative approaches in which the subject of this research are the teacher and 28 students of the fifth grade. The result of this research  was to show of the increasing of the plan, process, and learning outcomes. In conclusion, role playing method can increase the student’s learning outcomes in IPS learning. Keyword: Learning outcomes, role playing